Extraction and Functional Group Analysis of Gossypol from Cottonseed Meal - KUMAR, MANOJ; POTKULE, JAYASHREE; SAXENA, SUJATA (Cotton Research Journal, 2021)
Gossypol is a polyphenolic aldehydic compound which has been studied for its versatile biological activities. The extraction of gossypol from cottonseed meal was attempted using acidified solvent system. Mixture of acetone: ethanol and water (70:20:10) at 4.5 pH with solid-to-liquid ratio of 1:20 can be considered as best conditions for the extraction of gossypol. The purity and presence of specific functional groups was confirmed using Fourier Transform Infrared (FTIR) spectroscopy. Study will give a basis to further optimize the protocol for efficient extraction of gossypol form cottonseed meal for possible applications in agriculture, medicine and pharmaceuticals.